COW RAW MILK QUALITY AND ITS FACTORS OF INFLUENCE IN RELATIONSHIP WITH MILK PRICE - Agatha POPESCU; Elena ANGEL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents cow raw milk quality and its influence factors in connection with milk price based on a proper approach of the topic using analysis, synthesis, deduction which helped to establish "the state-of art" in the field of the authors' expertise, emphasizing on the particular factors which contribute to the improvement of milk quality which influence milk price in the EU, USA and other countries. Milk quality is determined by milk composition especially by fat and protein percentages, by the sensory, physical and chemical characteristics. Milk quality is assessed from a hygienic point of view in terms of Total Bacteria Counts (TBC) and Bulk Tank Somatic Cells Counts (BTSCC) whose level should be lower than the maximum thresholds mentioned by EU and USA standards in force, as well as regarding the aflatoxins and antibiotics content. The payment system for the quality of milk and the competition between suppliers and processors for milk supply encourages dairy farmers to produce more milk and of high quality. In this purpose, they have to improve breeding, feeding, hygiene and keep under control mastitis, treatments with antibiotics and other medicines and to produce high quality forages without aflatoxins. The reduction of TBC and BTSCC in raw milk will assure food safety and will increase shelf life of milk and dairy products. Business development in dairy farming has to keep pace with the changes in the internal and international markets. Farmers should become aware that they play an important role in raising milk demand and offer of high quality milk and dairy products.